THE INFLUENCE OF EMOTIONAL INTELLIGENCE ON THE DEVELOPMENT OF ASSERTIVENESS IN INDIVIDUALS - Філоненко, Мирослава; Мякіннікова, Ірина (SWorldJournal, 2026)
In modern psychology, the interaction between emotional self-regulation and social behavior remains a critical area of study. Assertiveness, as the ability to defend personal boundaries respectfully, is often hindered by emotional instability or low self-